1995
DOI: 10.1002/anie.199522271
|View full text |Cite
|
Sign up to set email alerts
|

Selective Syntheses of 1,3‐Diphosphacyclobutadiene, Dewar‐1,3,5‐triphosphabenzene, 1,3,5‐Triphosphabenzene, and 1,3,5,7‐Tetraphosphabarrelene by Cyclooligomerization of Phosphaalkynes

Abstract: Dcdic,uted to ProfiJssor MorIjrcd Regit: on ihi, o i n r s i o t i qf'kis 60th birtlidu,rThe rcccntly described synthesis of the 1,3.5,7-tetraphosphabarrelene complex 3 from rerr-butylphosphaacetylene 1 and bis-(cyc1ooctatetraene)zirconium [Zr(~ot),]"~ led to the assumption that the 12-valence electron fragment [cotM], formed as an intermediate by elimination of one of the two cot ligands, is an ideal tetnplatc for cyclooligomerizations of phosphaalkynes. Phosphaalkynes are known to cyclodimerize on the 14-val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
51
0
5

Year Published

1998
1998
2003
2003

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 36 publications
2
51
0
5
Order By: Relevance
“…[243] This experimental picture is rather surprising in the light of recent theoretical studies which indicate that all of the diphosphinine isomers show extensive cyclic delocalization, with the lowest energy form being the unknown 1,2-diphosphinine. [244,245] The much-sought-after 1,3,5-triphosphinine was first prepared by Binger et al [246] The best method for its preparation relies on the trimerization of phosphaalkynes in the presence of a vanadium(v) imido complex [see Eq. (48)].…”
Section: H 4 P]mentioning
confidence: 99%
“…[243] This experimental picture is rather surprising in the light of recent theoretical studies which indicate that all of the diphosphinine isomers show extensive cyclic delocalization, with the lowest energy form being the unknown 1,2-diphosphinine. [244,245] The much-sought-after 1,3,5-triphosphinine was first prepared by Binger et al [246] The best method for its preparation relies on the trimerization of phosphaalkynes in the presence of a vanadium(v) imido complex [see Eq. (48)].…”
Section: H 4 P]mentioning
confidence: 99%
“…Recently, we have shown that synthetic dinuclear and trinuclear [7] metallophosphodiesterases based on calix [4]arenes [8] exhibit a very high catalytic activity in the transesterification of the RNA model substrate 2-hydroxypropyl-p-nitrophenyl phosphate (HPNP). [6,9,10] Here we report that 1-Zn 3 efficiently catalyzes the cleavage of RNA dinucleotides (3',5'-NpN) by the cooperative action of the Zn II centers, with high rate enhancement and significant nucleobase specificity. The heterotrinuclear complex 1-Zn 2 Cu is even more active; it mimics phosphodiesterases with a heterotrinuclear metal cluster including a Zn II center in the active site.…”
mentioning
confidence: 95%
“…The apparent pK a of a Zn II -bound water molecule in 3-Zn is 7.9; [9] the value is lower for 1-Zn 3 due to hydrophobic and cooperative effects. [9,10] Therefore, it is likely that at pH 8 one or two Zn II centers in 1-Zn 3 are coordinated by a hydroxide ion. Furthermore, the activity reaches a Supporting information for this article is available on the WWW under http://www.wiley-vch.de/home/angewandte/ or from the author.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1995, 2,4,6-tri-tert-butyl-1,3,5-triphosphabenzene (1) was first reported, prepared through the trimerization of tert-butylphosphaacetylene (or 3,3-dimethyl-1-phospha-1-butyne), together with its valence isomer 2; [1] the structure of 1 was established in 1998. [2,3] Oligomerization of tert-butylphosphaacetylene has been utilized for the construction of various types of five-membered heterocyclic systems containing polycyclic systems.…”
mentioning
confidence: 99%